Effect of Commute Satisfaction on Subjective Well-Being: A Case Study during Covid-19 - Monge Solís, Fernando (2026)
To guide transportation and mobility policy toward well-being, it is essential to conceptualize well-being through travel-related satisfaction. This study surveyed members of the University of Costa Rica (UCR) community using structural equation modeling (SEM). An online questionnaire, administered via convenience sampling in late 2020, generated responses processed in R to construct latent variables. The SEM framework examined relationships among these variables via regression and was complemented by multiple indicators, multiple causes (MIMIC) specification to assess the influence of sociodemographic and travel characteristics. Findings show that satisfaction with the daily commute to UCR has a direct and significant effect on overall well-being, even during the COVID-19 shift to virtual instruction. Travel time emerged as the most influential determinant of commute satisfaction. Furthermore, active, and private transport modes were associated with higher commute satisfaction and greater subjective well-being than public transport. Limitations concern sample representativeness due to convenience sampling and pandemic-related mobility restrictions, which may constrain the generalizability of these results to post-pandemic contexts or other populations.